Transcriptome Meta-Analysis Associated Targeting Hub Genes and Pathways of Drought and Salt Stress Responses in Cotton (Gossypium hirsutum): A Network Biology Approach - Bano, Nasreen; Fakhrah, Shafquat; Mohanty, Chandra Sekhar; Bag, Sumit Kumar (Frontiers in Plant Science, 2022)
Abiotic stress tolerance is an intricate feature controlled through several genes and network in plant system. In abiotic stress, salt and drought are well known to limit the cotton productivity. Transcriptomics meta-analysis has arisen as robust method to unravel the stress-responsive molecular network in crops. In order to understand drought and salt stress tolerance mechanisms, meta-analysis of transcriptome studies are crucial. To confront these issues, here, we have given details of genes and networks associated with significant differential expression in response to salt and drought stress. The key regulatory hub genes of drought and salt stress condition having notable association with functional drought and salt stress responsive (DSSR) genes. In network study, nodulation signalling pathways2 (NSP2), Dehydration-responsive element1 D (DRE1D), ethylene response factor (ERF61), cycling DOF factor 1(CDF1) and tubby like protein 3 (TLP3) genes in drought and tubby like protein 1 (TLP1), thaumatin-like proteins (TLP), ethylene-responsive transcription factor ERF109 (EF109), ETS-Related transcription Factor (ELF4), and Arabidopsis thaliana homeodomain leucine-zipper gene (ATHB7) genes in salt showed the significant putative functions and pathways related to providing tolerance against drought and salt stress conditions along with the significant expression values. These outcomes provide potential candidate genes for further in-depth functional studies in cotton, which could be useful for the selection of improved genotype of Gossypium hirsutum against drought and salt stress conditions.